2022
DOI: 10.1186/s12879-022-07856-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination in pregnancy: views and vaccination uptake rates in pregnancy, a mixed methods analysis from SAIL and the Born-In-Wales Birth Cohort

Abstract: Background Vaccine hesitancy amongst pregnant women has been found to be a concern during past epidemics. This study aimed to (1) estimate COVID-19 vaccination rates among pregnant women in Wales and their association with age, ethnicity, and area of deprivation, using electronic health record (EHR) data linkage, and (2) explore pregnant women’s views on receiving the COVID-19 vaccine during pregnancy using data from a survey recruiting via social media (Facebook, Twitter), through midwives, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…The data in this study suggest that the proportion of pregnant women attending ANC clinic who had been vaccinated for COVID 19 vaccine was 27% lower compared to some other countries like the United States (40%), England (53.1%) and Saudi Arabia (57.1%) 13,15 . Low vaccine uptake might be a result of late launch of COVID 19 vaccine usage among pregnant women in Tanzania compared to other countries.…”
Section: Discussionmentioning
confidence: 57%
“…The data in this study suggest that the proportion of pregnant women attending ANC clinic who had been vaccinated for COVID 19 vaccine was 27% lower compared to some other countries like the United States (40%), England (53.1%) and Saudi Arabia (57.1%) 13,15 . Low vaccine uptake might be a result of late launch of COVID 19 vaccine usage among pregnant women in Tanzania compared to other countries.…”
Section: Discussionmentioning
confidence: 57%
“…Caribbean, Any Other Mixed/Multiple Ethnic Background. 4 Comprises of African, Any Other Black Background, Caribbean 5 Comprises of Any Other Ethnic Group, Arab, Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of information and changes in guidance and recommendations surrounding vaccination in pregnancy during the COVID-19 pandemic, this eventually resulted in some hesitancy among expectant mothers to receive vaccinations [4]. Although there is growing evidence that COVID-19 vaccine is safe and effective for pregnant women, vaccine hesitancy is still a signi cant issue [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is interesting to highlight the fact that the vaccination rate is much higher in Israel (43.3%) than in the USA (27.3%) and other countries (12.8%) [ 58 ]. Additionally, several other studies found a lower vaccination rate among pregnant women in Italy (49.4%) [ 44 ], Spain (56%) [ 45 ], Wales (32.7%) [ 59 ], Canada (42.4%) [ 41 ], and the USA (44%) [ 60 ]. The higher vaccination rate in our study may be due to the fact that the studies in the meta-analysis were conducted from December 2020 to September 2021, while our study was conducted from December 2021 to March 2022.…”
Section: Discussionmentioning
confidence: 99%